2012
DOI: 10.1037/a0023800
|View full text |Cite
|
Sign up to set email alerts
|

Motivation and maltreatment history among youth entering substance abuse treatment.

Abstract: Research has established that maltreatment experiences are common in the life histories of youth with substance abuse problems, and efforts are now moving in the direction of enhancing our understanding of the unique clinical presentations and treatment needs of this population. The current study endeavored to contribute to this body of research by examining associations between experiences of maltreatment and levels of motivation among youth entering outpatient substance abuse treatment. Upon admission, 188 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
1
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 38 publications
3
17
1
3
Order By: Relevance
“…As a matter of fact, women with physical and/or sexual abuse presented with higher rates of treatment dropout. These results support those obtained in previous studies in which the history of abuse is related to treatment dropout (Claus & Kindleberger, 2002;Fernández-Montalvo et al, 2015) and contradict the results from studies of addicted youth who have suffered childhood abuse, who showed a greater adherence to therapy (Rosekranz, Henderson, Muller, & Goodman, 2011;Slesnick, Kang, & Aukward, 2008).…”
Section: Discussionsupporting
confidence: 78%
“…As a matter of fact, women with physical and/or sexual abuse presented with higher rates of treatment dropout. These results support those obtained in previous studies in which the history of abuse is related to treatment dropout (Claus & Kindleberger, 2002;Fernández-Montalvo et al, 2015) and contradict the results from studies of addicted youth who have suffered childhood abuse, who showed a greater adherence to therapy (Rosekranz, Henderson, Muller, & Goodman, 2011;Slesnick, Kang, & Aukward, 2008).…”
Section: Discussionsupporting
confidence: 78%
“…Some research suggests that feelings of shame can arise as a consequence of using substances (Arentzen, 1978; Blume, 1990; Cook, 1987; Corrigan, Watson & Miller, 2006; Fossum & Mason, 1986; Luoma et al, 2007; O’Connor et al, 1994; Reed, 1987), and, of the papers reviewed here, one suggests that, amongst those who already use substances problematically, shame may have a positive impact by increasing motivation to seek treatment. In their study of 188 16–24 year-olds entering treatment for moderately-problematic substance use, Rosenkranz et al (2012) found that those individuals who reported greater shame-proneness were more likely to recognize their substance use as problematic and to seek treatment. Some research suggests that these individuals demonstrate superior treatment outcomes (Williams et al, 2008), but their data were subject to disclosure biases.…”
Section: Resultsmentioning
confidence: 99%
“…Some research suggests that feelings of shame can arise as a consequence of using substances (Arentzen, 1978;Blume, 1990;Cook, 1987;Corrigan et al, 2006;Fossum & Mason, 1986;Luoma et al, 2007;O'Connor et al, 1994;Reed, 1987), and , of the papers reviewed here, one suggests that, amongst those who already use substances problematically, shame may have a positive impact by increasing motivation to seek treatment. In their study of 188 16-24 year-olds entering treatment for moderately problematic substance abuse, Rosenkranz, Henderson, Muller, & Goodman (2012) found that those individuals who reported greater shameproneness were more likely to recognise their substance misuse and seek treatment.…”
Section: The Role Of Sexual Abuse In the Development Of Shamementioning
confidence: 99%
“…However, the data were subject to disclosure biases, and Rosenkranz et al (2012) used a measure of treatment motivation which conflates proneness to shame with motivation to seek treatment, and which included items (e.g., If I remain in treatment it will probably be because I'll feel very bad about myself if I don't) open to being interpreted as either 'shame' or 'guilt' by participants.…”
Section: The Role Of Sexual Abuse In the Development Of Shamementioning
confidence: 99%
See 1 more Smart Citation